2016
DOI: 10.1177/1471301216659608
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment challenges and strategies: Lessons learned from an early-stage dyadic intervention (innovative practice)

Abstract: An increasing number of family caregivers are seeking services and support due in large part to the dramatic increase in the number of older adults obtaining dementia diagnoses. This paper describes barriers and challenges experienced by our research team in recruiting early-stage dementia caregiving dyads into research studies. Effective recruitment and screening strategies to address these barriers are also discussed. Recruitment and enrollment success depends on these strategies as well as having well-train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Currently, family members supporting a person with early stages of dementia are also neglected in the literature (Szabo, Whitlatch, Orsulic-Jeras, & Johnson, 2016). This present study also had a limited number of participants from these understudied subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, family members supporting a person with early stages of dementia are also neglected in the literature (Szabo, Whitlatch, Orsulic-Jeras, & Johnson, 2016). This present study also had a limited number of participants from these understudied subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…the Reitman Center at Mount Sinai Hospital), and online support groups for caregivers (refer to Appendix F for all the recruitment documents used in this study). Research has shown that this strategy is particularly successful because of the close relationships that referral organizations and staff have with potential participants (Szabo, Whitlatch, Orsulic-Jeras, & Johnson, 2016). Social media recruitment strategies were also employed, such as posting in Facebook support groups and asking organizations to re-tweet or tweet recruitment notices on Twitter.…”
Section: Recruitmentmentioning
confidence: 99%
“…Having well-trained recruitment personnel who understood the study and the community was important (Szabo, Whitlatch, Orsulic-Jeras, & Johnson, 2016). Employing well-trained, recruiters who embraced a strengths-based perspective of AA fathers and families was the third component of the DAAD Study recruitment model.…”
Section: Recruitment Per Sonnelmentioning
confidence: 99%